SOCIAL CONSTRUCTION OF THE USE OF HABBATUS SAUDA PRODUCTS AMONG STUDENTS OF THE QUR'AN AND TAFSIR UIN MAULANA MALIK IBRAHIM MALANG - Nurul Istiqomah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
Habbatus sauda is one of the herbal plants that was known at the time of the Prophet. The benefits of Black Seed are found in the hadith of the Prophet. The use of Black Seed is quite appreciated in Indonesian society with its various processing and packaging. First, habbatus sauda is an ingredient that is packaged in herbal medicine in the form of capsules, real seeds, and oil. Both habbatus sauda are used as additional ingredients in bath soap, shampoo, and kitchen furniture laundry soap. This research will focus on care products that are used in their daily homes such as soap and shampoo whose composition uses Black Seed. This research is a type of field research. The method used is a qualitative method. The approach used in this study is a social construction approach. It is important to discuss this with social construction in order to reveal how externalization, objectification, and internalization occur in the use of this product. The results of this article are externalization described by understanding Islamic teachings that they have received by choosing properly any product to be used, including paying attention to the ingredients listed on the product because indirectly the halal label and according to the Sunnah of the Prophet as Islamic representation. Objectification described by changing patterns of respondent behavior being more selective when buying a product, paying more attention to halal labels and according to the Sunnah. Internalization is characterized by influences from the immediate environment and advertising media.